Conflict and polarisation on social media caused by the Russia-Ukraine War: The case of Ekşi Sözlük - Tolga Gürocak (Connectist Istanbul University Journal of Communication Sciences)
There has been an increase in ideological and political polarisation in Türkiye. Society is divided into dichotomies such as modern-traditional, religious-secular, right-left, Turkish-Kurdish, and Sunni-Alawi; the distinction is not limited to these. The polarisation in Türkiye is similarly increasing on Ekşi Sözlük1 , one of the largest internet communities according to visit and interaction rates in Türkiye. This study aims to reveal the reasons and forms of polarisation caused by the Russia-Ukraine War among Ekşi Sözlük writers who were not party to the war, and it is significant in revealing the severity of polarisation in Türkiye. For this purpose, 8.144 entries on the thread were analysed using qualitative content analysis under nine headings. It was found that the parties were shaped on the axis of Russia and Ukraine/ the North Atlantic Treaty Organization (NATO)/the United States of America (USA) dualism. The majority of these entries increase polarisation by affirming the actions of the side they consider close to themselves. The conflict between the defenders of the two sides ranges from insulting opposing views to insulting other authors. The proportion of polarising entries in the headline was close to that found in other similar studies on polarisation in recent years.